Mobile App Service Quality Dimensions and Requirements for Mobile Shopping Companion Apps - Tobias Wulfert (Junior Management Science (JUMS), 2019)
The increasing utilization of mobile apps for shopping leads retailers to provide customers with dedicated mobile shopping companion apps to create an omni-channel shopping experience involving traditional brick-and-mortar, electronic and mobile business. Mobile shopping companion apps extend the traditional and electronic services of brick-and-mortar retailers by an additional mobile channel providing the customer with a digital companion supporting the shopping within and outside the stores using mobile technology. A twofold approach is pursued in this thesis. Firstly, a structured literature review is conducted to identify candidate dimensions for developing a scale for measuring the service quality of mobile shopping companion apps. Secondly, design requirements for improving the service quality of these mobile apps are deduced from online customer reviews of three exemplary mobile shopping companion apps applying a qualitative content analysis. The mobile app service quality of mobile shopping companion apps can be measured using a hierarchical and multi-dimensional scale consisting of three primary dimensions, seven secondary dimensions and 22 related items. The primary dimensions interaction quality, environment quality and outcome quality structure the secondary dimensions responsiveness, information, security and privacy, design, performance, technical reliability and valence. Based on these dimensions, 22 implementation guidelines and 14 service design requirements are derived as potential areas for optimizing the mobile app service quality of mobile shopping companion apps and achieving a high overall service quality. A mobile shopping companion app should include a set of features consisting of 16 features from three different areas. Results show that measuring the service quality of mobile shopping companion apps require for a tailored measurement scale. Equally, design requirements are proposed for this particular category of mobile apps. Retailers should provide a single mobile shopping companion app providing all features and mobile services to the customer.
Keywords: 650; mobile service; mobile commerce; shopping companion; service quality